2017
DOI: 10.1021/acs.jpcc.7b05354
|View full text |Cite
|
Sign up to set email alerts
|

Does Surface Chirality of Gold Nanoparticles Affect Fibrillation of HSA?

Abstract: In order to demonstrate the influence of the surface chirality of the nanoparticles on amyloid fibrillation, the inhibiting effectiveness of the chiral gold nanoparticles, synthesized using the two enantiomeric forms (i.e., d- and l-) of glutamic acid, toward the fibrillation of human serum albumin (HSA) has been investigated. Here the enantiomers of glutamic acid are used as both reducing and stabilizing/capping agents. It is found that the surface chirality is the only major difference between the d-glutamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 76 publications
(140 reference statements)
2
23
0
Order By: Relevance
“…15 AuNPs have also exhibited tremendous potency in the management of oxidatively stressed conditions through quenching of free radical species. 16,17 AuNPs have been strategically explored as one platform for studying the influence of nanosurface charge, 18 surface chirality, 19 shape and size 20 on protein fibrillation.…”
Section: Introductionmentioning
confidence: 99%
“…15 AuNPs have also exhibited tremendous potency in the management of oxidatively stressed conditions through quenching of free radical species. 16,17 AuNPs have been strategically explored as one platform for studying the influence of nanosurface charge, 18 surface chirality, 19 shape and size 20 on protein fibrillation.…”
Section: Introductionmentioning
confidence: 99%
“…Surface functionalization with peptides : Tryptophan, tyrosine [83] or glutamic acid [84] as NP coatings have allowed fibril inhibition and even disaggregation. Glutamic acid‐functionalization revealed that chirality affects amyloid fibrillation; AuNPs bearing the d ‐enantiomer were more efficient with human serum albumin (HSA) [84] .…”
Section: Nanochaperones To Treat Misfolding Diseasesmentioning
confidence: 99%
“…[80] Inhibitory activities of bare (citrate) AuNPs were also observed with Ab [81] and insulin; [82] fibrillation was significantly delayed and the final aggregate structure,s hape,a nd density were altered. vi) Surface functionalization with peptides: Tr yptophan, tyrosine [83] or glutamic acid [84] as NP coatings have allowed fibril inhibition and even disaggregation. Glutamic acid-functionalization revealed that chirality affects amyloid fibrillation;A uNPs bearing the d-enantiomer were more efficient with human serum albumin (HSA).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Glutamic acid-functionalization revealed that chirality affects amyloid fibrillation;A uNPs bearing the d-enantiomer were more efficient with human serum albumin (HSA). [84] b-sheet breaker peptides,w hich recognize the hydrophobic domain of amyloidogenic proteins and interfere with b-structured aggregates,h ave also been used to increase the adhesion of Ab to NPs and enhance inhibition over fibrillation. LV FFARK-functionalized NPs restricted Ab42 conformational changes,redirected its aggregation into unstructured, off-pathway aggregates and reduced Ab toxicity.…”
Section: Angewandte Chemiementioning
confidence: 99%